Coign of vantage and action: Considering California's local accountability and school finance plans for English learners - Julian Vasquez Heilig; Lisa S. Romero; Megan Hopkins (Arizona State University, 2017)
Local control has been a bedrock principle of public schooling in America since its inception. In 2013, the California Legislature codified a new local accountability approach for school finance. An important component of the new California Local Control Funding Formula (LCFF) approach is a focus on English learners (ELs). The law mandates that every school district produce a Local Control Accountability Plan (LCAP) to engage the local community in defining outcomes and determining funding for ELs. Based on an exploratory analysis of a representative sample of LCAPs, we show that, although California's new approach offered an opportunity to support locally-defined priorities and alternatives to top-down accountability, few if any districts had yet taken full advantage of the opportunity. That is, the school districts in our sample had not yet engaged with the local community to facilitate significant changes to accountability or redistribution of funding and resources to support educational equity for ELs.